Economic Analysis of Recyclable Waste Management Systems in Bheemdatt (Sudurpaschim Spectrum, 2024)
This study investigates the economic analysis of recyclable waste management systems in Bheemdatt Municipality, Kanchanpur, Nepal. It aims to analyze the current state of recyclable waste management, focusing on understanding the situation and analyzing economic perspectives. Employing a mixed-methods approach, it utilizes Key Informant Interviews (KII) and semi-structured questionnaires for primary data collection, supplemented by secondary data sources. The findings highlight despite challenges such as poor technology and limited municipal involvement, the municipality demonstrates resilience in regulating scrap collection activities and revenue generation through taxation, facilitated by private sectors, underscoring the economic viability of recycling initiatives. Major findings from analysis shows an increasing ratio of e-waste, poor technological and management practices by the municipality, and a notable presence of female workers in the waste management sector. The study concludes that e-waste, such as batteries and electronic devices, is on the rise in municipal waste, offering recyclable possibilities and contributing significantly to the recyclable materials. Additionally, it can be concluded that recyclable waste is economic viability of recycling initiatives for local government in which female workers are more prevalent than male workers in the collection and management of recyclable waste in the study area. Continuous review and adjustment of taxation policies, investment in recycling infrastructure, promotion of circular economy principles, exploration of emerging market opportunities, and capacity building for waste collectors and scrap center workers are recommendations of the study which can enhance the economic sustainability of recycling initiatives for the local government.